Trust in young women with long distance relationship - Nugraha, Andreas Corsini Widya; Abdillah, Rijal; Nurfitriani, Aisyah; Febrianti, Zahra Dwiana (Universitas Sarjanawiyata Tamansiswa, 2024)
Conflicts that occur in someone who is in a Long Distance Relationship are caused by a lack of trust or trust in their partner. Previous studies have shown that low trust involves misunderstandings, poor communication, and distrust. The key to a successful Long Distance Relationship is communication and openness to build trust. This study aims to explore the dynamics of trust in early adult women when establishing long-distance relationships. The Data were obtained using in-depth interviews with two early adult women who were in a long-distance relationship. The approach used is narrative qualitative in which a purposive sampling technique is used to search for research subject data. The data were analyzed using narrative data analysis with the fusion of research themes through data coding. The results showed that trust in both subjects could increase and decrease depending on the behavior of their respective partners. Trust in both subjects in establishing a long-distance relationship can be maintained through the process of communication, openness (openness), and commitment, Trust in both subjects can decrease when miscommunication and subjects know that their partners are lying. In addition, both subjects were able to regain trust if each of the partners was willing to admit mistakes and apologize to both subjects so that they felt calm.